Integrated transport delivered? 3rd Wales transport conference : one day seminar (Thomas Telford, 2003)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of the third Wales Transport conference held in Cardiff on 16 May 2003.